The influence of subjective norms and self-efficacy on entrepreneurial intentions: A study on students - Prasepta, Rayhan Guna; Febrianti, Adjeng Mariana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of subjective norms and self-efficacy on entrepreneurial intentions. The subjects of this study were private students in the city of Bandung majoring in the faculty of economics and business who joined the HIPMI organization (Association of Young Indonesian Entrepreneurs). The sample in this study was the entire population of 100 students who had met the requirements. Data was collected by means of interviews and direct questionnaires to respondents, and path analysis was used in this study to analyze the data statistically. The subjective norm and efficacy factors support the entrepreneurial intention. The majority of students also have the intention to become entrepreneurs. This intention is because students have received entrepreneurship courses and environmental influences on the higher education HIPMI organization.